1995
DOI: 10.1002/eji.1830250916
|View full text |Cite
|
Sign up to set email alerts
|

The majority of murine VH12‐expressing B cells are excluded from the peripheral repertoire in adults

Abstract: We have previously demonstrated that at birth most productive (P) VH12 rearrangements in B10.H-2aH-4bp/Wts (2a4b) mice encode a ten-amino acid CDR3, and that a significant fraction of the expected repertoire is absent. We have now examined the adult VH12 CDR3 repertoire involving all four JH gene segments in both peritoneum and spleen. Of the 74 P VH12 rearrangements from these tissues 67 encode a CDR3 of ten amino acids and include a Gly in the fourth position (designated 10/G4). Most of these rearrangements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…This supports the hypothesis that the observed bias in V 4/5H L chain gene use by mature B cells in 6-1 mice (27) is due to an inability of non-V 4/5H L chains to support differentiation to the mature B cell stage. This is the third checkpoint in V H 12 B cell differentiation, after the pre-BI to pre-BII and the pre-BII to immature B checkpoints (26,29,39), that restricts V H 12 B cells primarily to the production of H and L chains that form an anti-PtC BCR and drives differentiation to B-1.…”
Section: Discussionmentioning
confidence: 99%
“…This supports the hypothesis that the observed bias in V 4/5H L chain gene use by mature B cells in 6-1 mice (27) is due to an inability of non-V 4/5H L chains to support differentiation to the mature B cell stage. This is the third checkpoint in V H 12 B cell differentiation, after the pre-BI to pre-BII and the pre-BII to immature B checkpoints (26,29,39), that restricts V H 12 B cells primarily to the production of H and L chains that form an anti-PtC BCR and drives differentiation to B-1.…”
Section: Discussionmentioning
confidence: 99%
“…His group has found that the development of B lineage cells with V H 12 rearrangements is constricted at several points, such that B cells with this H chain become progressively restricted to the prototypic anti-PtC BCR, even though the most frequently found V H 12 rearrangement generates a H chain capable of associating with SLC. Thus, at the pre-B stage, rearrangements containing CDR3 segments of 10 aa and with a glycine residue in the fourth position ("10/G4") are much more likely to be found among productive V H 12 sequences (70). A likely explanation for this preference is pre-BCR selection, such that most V H 12 rearrangements generate H chains that fail to associate with SLC, whereas those with the 10/G4 segment do and so can mediate progression to the late pre-B stage where L chain rearrangement takes place.…”
Section: Selection In B-1 B Cell Developmentmentioning
confidence: 99%
“…The surviving 5% are enriched in CDR3 sequences of 10 amino acids and include many with a glycine (Gly) in the fourth position (referred to as 10/G4). The 10/G4 CDR3 is used by almost all V H 12‐expressing B1 cells specific for PtC (27). There is no mechanistic bias in V H 12 rearrangement that could account for the enrichment of 10 amino acid CDR3s, beacuse in pre‐B1 cells of µMT mice, where selection cannot occur, there is no enrichment for CDR3 length or sequence (27).…”
Section: Selection At the Pre‐b‐cell Stagementioning
confidence: 99%